2021
DOI: 10.1111/jmft.12542
|View full text |Cite
|
Sign up to set email alerts
|

Interfamily Therapy, a multifamily therapy model settled in infant‐juvenile mental health services of Havana (Cuba): A qualitative study from participants’ perspectives

Abstract: Interfamily therapy (IFT) is a specific model for multifamily therapy (MFT) of recent expansion in Latin American and European countries. In IFT a multifamily group becomes a community of learning where professionals and family members establish collaborative relationships and participate in dialogues. This study used a qualitative phenomenological approach to explore the participants’ perspective of 14 members and ex‐members of two IFT groups conducted in Infant‐Juvenile Mental Health Centers in Havana (Cuba)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Our study revealed a variety of complex mental health and well-being challenges faced by young prisoners, which are in line with other studies. For example, a study on infant–juvenile mental health services in Cuban prisons reported that feelings of guilt, tension and frustration were common among the participants (Ruiz‐Íñiguez et al , 2021). Another study with inmates in Colorado revealed that stress, fear, anxiety and other psychiatric symptoms were frequently experienced in this population (Binswanger et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed a variety of complex mental health and well-being challenges faced by young prisoners, which are in line with other studies. For example, a study on infant–juvenile mental health services in Cuban prisons reported that feelings of guilt, tension and frustration were common among the participants (Ruiz‐Íñiguez et al , 2021). Another study with inmates in Colorado revealed that stress, fear, anxiety and other psychiatric symptoms were frequently experienced in this population (Binswanger et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, it is important to understand young prisoners¨mental health and well-being and to identify what kind of support they need to improve their current and future situations (Ruiz-I ´n ˜iguez et al, 2021). Without a supportive environment and access to operating quality services, deterioration of the mental health and well-being of young prisoners might have substantial negative effects on their social and physical situation in the prisons (Chappell and Maggard, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It promotes self‐efficacy and has a potential preventive effect. Group cohesion is a predominant therapeutic factor in MFT (Hellemans et al, 2011; Ruiz‐Íñiguez et al, 2021), helping people not to feel alone but in a big family where there are people they can trust.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting qualitative study analyzes MFT benefits and therapeutic factors in the infant‐juvenile population, considering participants' perspectives. It concludes that MFT seems to be a useful therapeutic model for this population (Ruiz‐Íñiguez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation